Irregularities in Legal Procedures in The Cipulir Street Performer Case: An Analysis from Investigation to Pre-Trial - Maharani, Ni Made Anggi Dwita; Suwono, Frederica Celia; Abigail, Ielien Dorothy; Nadine, Nathanael; Masari, Stevanus (Devotion : Journal of Research and Community Service, 2025)
Pre-trial proceedings are a legal mechanism designed to control the actions of law enforcement officials, particularly in the process from investigation to prosecution. This study aims to analyze the role of pre-trial proceedings as a form of legal protection for victims of wrongful arrest, with a case study of street musicians in Cipulir who were named suspects without valid evidence. The method used is a normative juridical approach with descriptive analysis of legislation, legal doctrines, and relevant court decisions. The research results show that although pre-trial proceedings normatively have a strategic role in protecting the human rights of suspects, in practice there are still various weaknesses, including limitations in the scope of objects, the passive nature of pre-trial judges, and time constraints to resolve cases. The Cipulir case illustrates the failure of the pre-trial system to provide effective and responsive legal protection. Therefore, comprehensive legal reforms are needed, such as expanding the object of pre-trial proceedings, strengthening the role of judges, and increasing the capacity of law enforcement officials in guaranteeing procedural justice. This study recommends strengthening pre-trial proceedings as an instrument of judicial oversight in the Indonesian criminal justice system.